Il sacro in Durkheim e le sue definizioni - Paoletti, Giovanni (SocietàMutamentoPolitica, 2017)
Durkheim’s influential conception of the sacred, as the French sociologist formulated it after a quite long and complex elaboration, contains a fundamental dilemma: one should see the sacred as the apotheosis of the superior moral force of society, or as the need that every society has of material objects in order to think itself?